Assessment of knowledge, attitudes, and practices towards infection prevention among healthcare workers in Trinidad and Tobago - Unakal, Chandrashekhar G; Nathaniel, Anoop; Keagan, Bajnath; Alexandria, Bharat; Lauralee, Burgess; Varun, Chatoo; Reneé, Defour; Sarah, Duverney; Uniqué, Thurston; Akpaka, Patrick E. (International Journal Of Community Medicine And Public Health, 2017)
Background: The objective of the study was assessment of knowledge, attitudes, and practices (KAP) towards infection prevention among healthcare workers (HCW) in Trinidad and Tobago. Methods: A cross-sectional study was conducted among 300 HCWs from three regional hospitals in Trinidad and Tobago about their knowledge, attitude, and practice towards infection prevention in the country. All information’s were collected through interview using structured questionnaires. The data was collected from April to June 2016; thoroughly checked and cleaned for completeness before analysis with SPSS version 20 statistical software. The 95% confident interval and the p value were used to check for association between the dependent and independent variables. A p value of <0.05 was considered statistically significant. Finally, the findings of the study were explained using tables. Results: A total of 300 HCW participated in the study, with a 100% response rate. In this study only 20.3% respondents were knowledgeable, 46.7% had good attitude and 44% had good practices toward infection prevention, suggesting less than satisfactory scores in this study. Conclusions: The results highlight generally poor knowledge, attitudes and practices towards infection prevention in the three hospitals in Trinidad and Tobago. Therefore, policies and measures should be put in place to ensure regular training programs for HCW, providing strong understanding and a positive outlook on infection prevention.